Efficient synthesis of 4-sulfanylcoumarins from 3-bromo-coumarins: Via a highly selective DABCO-mediated one-pot thia-Michael addition/elimination process - Mostardeiro, Vitor B. (2020)
A facile and efficient protocol for the highly selective direct sulfanylation of 3-bromocoumarins under DABCO promotion, was developed. The transformation took place with aromatic and aliphatic thiols as well as with α,ω-dithiols, affording the expected products in very good to excellent yields. Simple and convenient ways to access 4-((ω-mercaptoalkyl) thio)coumarins and the dimeric 4,4′-(alkane-1,4-diylbis(sulfanediyl))bis(coumarins) were also devised with the use of α,ω-alkanedithiols in different ratios with regards to the starting 3-bromocoumarin. The transformation seems to proceed through the DABCO-mediated thia-Michael stereoselective addition of the thiolate anion to the α,β-unsaturated carbonyl system of the coumarin, followed by a DABCO-assisted stereoselective dehydrobromination of the resulting α-bromo carbonyl intermediate.